Sistem Senjata Otonom, Kecerdasan Buatan Militer, dan Imperasi Kontrol Manusia yang Bermakna: Sebuah Tinjauan Literatur - Muhamad Aria Armada Djojosugito (Institute of Advanced Knowledge and Science, 2025)
The proliferation of Autonomous Weapon Systems (AWS) based on artificial intelligence introduces complex challenges across legal, ethical, technical, and global policy dimensions. This literature review examines 26 academic articles published between 2014 and 2026, synthesized into seven thematic clusters: (1) definition and taxonomy of AWS, (2) compliance with International Humanitarian Law (IHL) and algorithmic transparency, (3) the concept and operationalization of Meaningful Human Control (MHC), (4) accountability and responsibility gaps, (5) human robot teaming and operational realities, (6) value based design and cross cultural perspectives, and (7) international governance and regulation. The findings indicate broad consensus that Meaningful Human Control represents a non negotiable principle, yet its operational definition remains debated. Key tensions emerge between performance and accountability, innovation and regulation, and universal values and cultural context. The review also identifies six urgent research gaps that require further academic and policy attention.